2016
DOI: 10.3747/co.23.2394
|View full text |Cite
|
Sign up to set email alerts
|

Can the Referring Surgeon Enhance Accrual of Breast Cancer Patients to Medical and Radiation Oncology Trials? The Enhance Study

Abstract: IntroductionThe accrual rate to clinical trials in oncology remains low. In this exploratory pilot study, we

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
(31 reference statements)
4
11
0
Order By: Relevance
“…In spite of prevailing ideals of patients’ self-management and shared decision-making, doctors continue to have a decisive role in determining their patients’ treatments. It is important to note that contrary to patients’ expectations, doctors do not always mention clinical trials [21], and, as our study indicates, will rarely mention existing opportunities for expanded access.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In spite of prevailing ideals of patients’ self-management and shared decision-making, doctors continue to have a decisive role in determining their patients’ treatments. It is important to note that contrary to patients’ expectations, doctors do not always mention clinical trials [21], and, as our study indicates, will rarely mention existing opportunities for expanded access.…”
Section: Discussionmentioning
confidence: 59%
“…Still, our respondents were rather assertive with regard to their health, and may have differed in this respect from other Dutch patients. Studies have found, for instance, that most patients are not actively looking for non-standard treatment options such as clinical trials, and tend to follow recommendations by their doctors instead [21, 28, 29]. Our respondents were generally less passive, and more actively involved in searching for and decision-making regarding treatment options.…”
Section: Discussionmentioning
confidence: 85%
“…Given that these novel agents will be added to a standard chemotherapy backbone, determining the optimal chemotherapy regimen should be regarded as a pressing research question. However, most physicians appeared to have minimal enthusiasm about the study overall, and developing a strategy to perform such a study would be challenging [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physicians, on the other hand, may feel obliged to move forward with research, here, their personal evaluation of the research may also play an important role. 48,49 However, physicians may also encounter uncertainties regarding the object of research and may have difficulties explaining clinical research which can also affect informed consent consultations. 8 A more general concern is the conflict of interest at play when physicians are conducting research at the same time of caring for patients, making it easier for physicians to identify and recruit research subjects.…”
Section: Background: Ethical Considerations Of Oncology Patients' Resmentioning
confidence: 99%